Immunosuppressive cells in acute myeloid leukemia: mechanisms and therapeutic target - Liu, Mengnan; Yang, Mengting; Qi, Yue; Ma, Yuting; Guo, Qulian; Guo, Ling; Liu, Chunyan; Liu, Wenjun; Xiao, Lan; Yang, You (Frontiers in Immunology, 2025)
Immunotherapy has emerged as a cornerstone strategy for augmenting therapeutic efficacy in acute myeloid leukemia (AML). The immunosuppressive AML microenvironment, characterized by profound immune dysfunction, critically impairs anti-leukemic immune surveillance. This immunologically hostile niche is principally governed by specialized immunosuppressive cell populations—notably regulatory T cells (Tregs), myeloid-derived suppressor cells (MDSCs), leukemia-associated macrophages (LAMs), and regulatory B cells (Bregs)—which collectively establish an immune-privileged sanctuary for leukemic cells. This review critically examines three fundamental aspects of these immunosuppressive regulators in AML pathogenesis: (1) their recruitment dynamics within the leukemic niche, (2) the molecular mechanisms underlying their immunosuppressive functions, and (3) current and emerging therapeutic approaches designed to neutralize their inhibitory effects. Through this comprehensive analysis, we aim to provide a mechanistic framework for developing more effective immunotherapeutic interventions against AML.